Effect of equilibration period on post thaw viability and membrane integrity of boar spermatozoa during conventional method of freezing - KHAN, M H; NATH, K C; DEKA, B C; KUMAR, SURESH; GOSWAMI, J; BASUMATARY, R; BARMAN, CHAMPAK (The Indian Journal of Animal Sciences, 2013)
The study was conducted to find out the effect of equilibration period on post thaw viability and membrane integrity of Hampshire (HS) and crossbred (CB) boar semen frozen with conventional method of freezing. Ejaculates (72) were collected (12 each from 3 Hampshire and 3 crossbred boars) during the study period. The semen samples having more than 75% initial motility and concentration above 100 million/ml were subjected to freezing. Before freezing, each semen sample was divided into 4 aliquots and kept for 0, 1, 3 and 5 h at 5°C for equilibration. Freezing was done by putting the filled and sealed straws on liquid nitrogen vapours and then plunged into liquid nitrogen. Results showed that overall mean motility and live sperm count of spermatozoa after equilibration and after thawing was significantly higher than at 3 and 5 h of equilibration. Mean acrosomal integrity and hypo-osmotic reacted spermatozoa, irrespective of breeds, recorded after equilibration was significantly higher in 0 and 1 h equilibration than in 3 and 5 h. However, after thawing, overall mean acrosomal integrity remained significantly higher in 1 h equilibration. No significant difference between the genetic groups was recorded in terms of motility, live sperm count and hypo-osmotic reacted spermatozoa after equilibration as well as after thawing. But, the acrosomal integrity was significantly higher in HS than in CB boars (66.25±1.05 vs 63.41±1.43) in semen samples equilibrated for 5 h. It may be concluded from the present study that shorter exposure of spermatozoa at 5 °C is beneficial for viability and membrane integrity whereas longer exposure tended to deteriorate the post thaw semen quality